Making CFS foundation law course generic: teachers' perception on the amendment of curriculum - Azizan, Puteri Amelia Norhananie; Termizi, Mazbah; Mohd Ramli, Rizq Fairuz (2014)
The present foundation law curriculum in the International Islamic University of Malaysia’s Centre for Foundation Studies offers specialised subjects that correlate with undergraduate law degree courses offered by the main campus. During the foundation year, students will be equipped with basic knowledge of the law and the current local and global issues. Students will also attain proficiency in the English language and basic skills in computer courses. Recently, it has been proposed that the streamlined system practised by all foundation programmes in Malaysian tertiary institutions should be repealed to make way for a standardised system. In general, when there is an implementation of change in the tertiary education system, the school or department involved will have to review and revise the curriculum. This would mean going through numerous approval processes and racing to meet curriculum deadlines. Our objectives, inter alia, are to re-evaluate the significance of establishing foundation law programme to prepare law students for higher degree education, to investigate the impact of generic curricula towards law teachers’ teaching performance, and to study the benefits and detriments law students may receive from learning in a generic module. Interviews will be conducted for qualitative data collection. Selected respondents consist of foundation law lecturers, law students and educationalists from IIUM Gombak with more than 5 years of teaching experience. Concerns have been expressed regarding whether students will have enough time to absorb the fundamental legal education they need to learn before heading on to their undergraduate stage; and whether teachers will be able to efficiently balance the demand of teaching law and other generic subjects in the new standardized system while meeting cu